Synthesis and characterization of aluminosilicate and zinc silicate from sugarcane bagasse fly ash for adsorption of aflatoxin B1 - Chalida Niamnuy; Sirada Sungsinchai; Prapaporn Jarernsamrit; Sakamon Devahastin; Metta Chareonpanich (My University, 2024)
Abstract Sugarcane bagasse fly ash, a residual product resulting from the incineration of biomass to generate power and steam, is rich in SiO 2 . Sodium silicate is a fundamental material for synthesizing highly porous silica-based adsorbents to serve circular practices. Aflatoxin B1 (AFB1), a significant contaminant in animal feeds, necessitates the integration of adsorbents, crucial for reducing aflatoxin concentrations during the digestive process of animals. This research aimed to synthesize aluminosilicate and zinc silicate derived from sodium silicate based on sugarcane bagasse fly ash, each characterized by a varied molar ratio of aluminum (Al) to silicon (Si) and zinc (Zn) to silicon (Si), respectively. The primary focus of this study was to evaluate their respective capacities for adsorbing AFB1. It was revealed that aluminosilicate exhibited notably superior AFB1 adsorption capabilities compared to zinc silicate and silica. Furthermore, the adsorption efficacy increased with higher molar ratios of Al:Si for aluminosilicate and Zn:Si for zinc silicate. The N 2 confirmed AFB1 adsorption within the pores of the adsorbent. In particular, the aluminosilicate variant with a molar ratio of 0.08 (Al:Si) showcased the most substantial AFB1 adsorption capacity, registering at 88.25% after an in vitro intestinal phase. The adsorption ability is directly correlated with the presence of surface acidic sites and negatively charged surfaces. Notably, the kinetics of the adsorption process were best elucidated through the application of the pseudo-second-order model, effectively describing the behavior of both aluminosilicate and zinc silicate in adsorbing AFB1.
Keywords: Mycotoxins in Agriculture and Food